An Explanation of the Volatility Disparity between the Domestic and Foreign Shares in the Chinese Stock Markets - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2003)
Return volatility is found significantly higher for the foreign shares (B shares) than for the domestic shares (A shares) traded in the Chinese stock markets. To explain this volatility disparity, we investigate the bid–ask spreads and estimate the market-making costs (informed trading and noninformed trading costs) for each stock. Our results show that the B-share market in China contains higher informed trading and other market-making costs than the A-share market. When informed trading and other cost components are accounted for, the volatility disparity between the A and B shares disappears. Thus, the higher volatility in the B-share market can be attributed to the higher market-making costs faced by B-share traders.